The Characteristics Elements of Being a Superstar : A Study of Entertaintment Industry - Yefta Christian (International Journal of Family Business Practices, 2023)
Introduction/Main Objectives: This study examines the characteristics of superstars in the entertainment industry in Indonesia, using the Korean entertainment industry as a reference for success. Background Problems: The motivation behind the study was to identify problems in the Indonesian entertainment industry and provide solutions for its development, as well as to improve its competitiveness with other countries. Novelty: The researchers used various sources to support their study and found ways to improve the Indonesian entertainment industry. Through interviews, the researchers identified complaints about the industry and realized the importance of government support and community involvement in enhancing its quality. Research Methods: The study employs a qualitative method, collecting data through interviews. Finding/Results: The researchers found that 50% of the participants were K-pop fans and 50% were not, and 85% of interviewees agreed that the Indonesian entertainment industry needed to address its problems and follow steps similar to those taken by Korea. Conclusion: Some limitations of the study included inappropriate sampling selection and a lack of balance in selecting participants. The researchers recommended that future studies be more precise in selecting participants and obtain data from professionals in the entertainment industry. Overall, the study provides insight into the challenges faced by the Indonesian entertainment industry and offers suggestions for its improvement.